Peran Financial Literacy dan Financial Technology dalam Membantu Perekonomian UMKM di Desa Bandar Khalipah - Sri Puji Lestari; Linzzy Pratami Putri; Dena Adella (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
Bandar Khalipah Village is a developing village, this is indicated by the many MSME actors in the village. However, MSME actors have low financial literacy and carry out sales transactions using manual or face-to-face methods. This study aims to determine the role of financial literacy and Financial Technology (FinTech) in improving the Economy of Micro, Small Medium Enterprises (MSMEs) in Bandar Khalipah Village. In this study using qualitative methods and the type of writing used is descriptive. The population in this study were 40 Micro, Small and Medium Enterprises (MSMEs) in Bandar Khalipah Village. In this study, the data analysis technique used is descriptive. The results of this study indicate that Financial Literacy and Financial Technology can improve the economy of MSME actors in Bandar Khalipah Village. Financial Literacy and Financial Technology make it easier for MSMEs to run their business, especially in sales transaction activities. MSMEs realize that knowledge of the functions, benefits and uses of fintech when used in making transactions can simplify and speed up the transaction process in running Micro, Small Medium Enterprises (MSMEs).